The Emerging Paradigm of Relational Self Psychology: An Historical Perspective. Issue 1 (2nd January 2021) - Magid, Barry; Fosshage, James; Shane, Estelle
ABSTRACT: This article describes the evolution of a critical dimension of self psychology that has evolved since Heinz Kohut's death, one characterized by the transition from a one-person to a two-person psychology. This transition involved, initially, the change in the analyst's role as limited to interpreting the patient's intrapsychically generated selfobject experiences of development, rupture, and repair, to an emergence into full personhood; second, a new emphasis on the analyst's subjectivity participating in a bi-directional relationship of mutuality rather than a unidirectional provision of needed functions; and finally, an overall approach to the therapeutic process as a complex, dynamic system. This emergent paradigm within self psychology we term relational self psychology. We illustrate its evolution through a historical review of critical papers that extended and transformed Kohut's original vision, which already contained the seeds of a genuinely intersubjective and relational model. We outline these changes in four sections: (I) "Empathy and Beyond, " detailing the concept's evolution within Kohut's writing and its subsequent elaboration; (II) "From Provision to Mutuality, " describing the movement beyond Kohut's focus on understanding and explaining and the mutative force of optimal frustration; (III) "You've Come a Long Way, Baby, " discussing infant research emphasizing face-to-face interaction and mutual regulation moving into the development of a truly bi-directional model of therapeutic action; and finally, (IV) "From Dyads to Systems, " integrating self psychology into a broader intersubjective, relational, dynamic system and theoretical context. Each section concludes with a bibliography of seminal-related articles that may offer a syllabus for further study.